Valuation of Crypto Projects/Assets - Ariepiev, Nikita; Svačina, Pavel, 1979-; Krabec, Tomáš, 1981-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis is devoted to the problem of valuation of cryptocurrency assets, which is becoming more and more relevant for the financial sector. The purpose of the work is to analyze the existing methods and approaches to the valuation of these assets with a focus on their applicability in practice. The paper supplemented the theoretical part with an actual methodology for the valuation of cryptocurrencies, which was then tested on specific examples. In the conclusion of the work it was confirmed that traditional valuation methods are partially applicable, but for a comprehensive analysis of cryptocurrency assets it is necessary to adapt the methodology taking into account the specific characteristics of these assets. The results of the work have significance not only for finance professionals, but also for novice investors who can use new techniques for safer and more efficient valuation of cryptocurrencies.
Vedoucí práce: Pavel Svačina
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance a oceňování podniku [obor dipl. práce]; diplomové práce; master's theses